Electrochromic Effect in Titanium Carbide MXene Thin Films Produced by Dip‐Coating. (3rd March 2019) - Salles, Pol; Pinto, David; Hantanasirisakul, Kanit; Maleski, Kathleen; Shuck, Christopher E.; Gogotsi, Yury
Abstract: MXenes, a large family of 2D transition metal carbides and nitrides, have shown potential in energy storage and optoelectronic applications. Here, the optoelectronic and pseudocapacitive properties of titanium carbide (Ti3 C2 T x ) are combined to create a MXene electrochromic device, with a visible absorption peak shift from 770 to 670 nm and a 12% reversible change in transmittance with a switching rate of <1 s when cycled in an acidic electrolyte under applied potentials of less than 1 V. By probing the electrochromic effect in different electrolytes, it is shown that acidic electrolytes (H3 PO4 and H2 SO4 ) lead to larger absorption peak shifts and a higher change of transmittance than the neutral electrolyte (MgSO4 ) (Δλ is 100 nm vs 35 nm and Δ T 770 nm is ≈12% vs ≈3%, respectively), hinting at the surface redox mechanism involved. Further investigation of the mechanism by in situ X‐ray diffraction and Raman spectroscopy reveals that the reversible shift of the absorption peak is attributed to protonation/deprotonation of oxide‐like surface functionalities. As a proof of concept, it is shown that Ti3 C2 T x MXene, dip‐coated on a glass substrate, functions as both transparent conductive coating and active material in an electrochromic device, opening avenues for further research into optoelectronic and photonic applications of MXenes. Abstract : The optoelectronic and pseudocapacitive properties of titanium carbide (Ti3 C2 T x ) MXene are combined to create a MXene electrochromic device, exhibiting a reversible shift of the absorption peak from 770 nm (green) to 670 nm (blue). The discovery of MXenes as electrochromic materials can open a large field of different color devices depending on the composition.